ANALYZING FACTORS INFLUENCING INDONESIAN MOBILE GAMERS ON REPURCHASE INTENTION IN FREEMIUM MOBILE GAME WITH PERVAL (The Indonesian Journal of Business Administration, 2021)
In 2018, Indonesia’s players spent a total of $1.1 billion on games in 2018[1], making it one of the biggest games markets in Southeast Asia. The rapid growth of mobile and internet users in Southeast Asia attracted many game developers’ attention to develop their products at SEA. The increased use of smartphones in SEA reflects the region’s mobile game market that offers revenue of $ 2.6 billion in 2019, with year-on-year growth of + 17.4%. This makes the world’s fastest-growing region for online game revenue. Mobile is growing the fastest, with the share of game revenue growing from 67,3% in 2018 to 69,4% in 2019. It means that the mobile-focused game publishers are dominating the SEA’s game market. The high-potential growth region was making companies both overseas and local contesting for a piece of it.The competition among game publishers in Indonesia dominated by international game publishers makes it very competitive and challenging for local game publishers to compete. It is found that the total spent of Indonesian players 99% goes to international competitions for all platforms ranging from mobile to PC to console, while 1.2% goes to locally-made games[2]. The author utilized the PERVAL Framework because it showed that perceived value is a strong indicator of consumer behavior, decision-making processes, and a competitive advantage for a product and service. Also, empirical studies are rare in assessing PERVAL concerning online game players’ attitudes, intentions, and behavioral intentions. To create novelties, the author modified the original PERVAL Framework based on the research’s needs. There are 390 respondents declared to meet the respondents’ requirements from the questionnaire that has been distributed. Next, the author processed the respondents’ data by utilizing SmartPLS to conduct a Path Analysis. The findings show that emotional value, price value, quality value, social value, satisfaction, addiction, and user loyalty significantly influence repurchase intention to buy virtual items at Mobile Legends.Keywords: PERVAL Framework, Repurchase Intention, Online Mobile Game, Mobile Legends